Influência do uso de agrotóxicos na qualidade dos recursos hídricos da região do perímetro irrigado Jaguaribe-Apodi/CE - Milhome, Maria Aparecida Liberato (2011)
The region of Baixo Jaguaribe-CE is considered one of the most important areas of irrigated orcharding in Ceara state. In recent years there has been a growing number of cancer cases in the cities of North Limoeiro and Quixeré and may associated with indiscriminate use of pesticides. The research aimed to study the influence of pesticide use in the contamination of surface and groundwater used for irrigation and human consumption, located in the vicinity of irrigation projects in the region of Baixo Jaguaribe. The first step was a survey of 37 active ingredients applied by farmers in major crop in the region. In the second stage models were used to evaluate the potential for contamination of pesticides in surface water and groundwater, based on their physicochemical properties. Screening method of EPA and GUS index were applied for analysis of potential contamination to groundwater and Goss method for surface waters. Through the results, we identified the pesticides used by farmers in the Baixo Jaguaribe with greater potential for contamination, among which were selected atrazine, methyl parathion, chlorpyrifos, fenitrothion, triazophos, propiconazole, difenoconazol and azoxystrobin for water monitoring. In addition, pesticides bentazone, molinate, malathion and pendimentalina established by legislation, were also monitored. The third step was conducted to develop methods for chromatographic analysis of selected pesticides using SPME / GC-MS and SPE / HPLC-UV. SPME procedure was optimized by selection of fiber, studied the effect of pH, equilibrium time and variation of sample volume. The fourth stage was carried to the sampling of water samples in 15 points more susceptible to contamination (7 points Dija canal and reservoirs, and 8 wells) According to the results detected the pesticide propiconazole, difenoconazole, azoxystrobin, chlorpyrifos, methyl parathion, atrazine and triazophos, which belong to a variety of chemical groups and different types of use. Pesticides propiconazole and difenoconazole showed the highest concentration levels detected (3.84 to 10.14 and 0.33 to 6.93 μg/L, respectively). About 80% of the samples had levels above the established by the European community, however within the Brazilian standards. Despite the concentration level of pesticides detected is within the acceptable daily intake of water, this should not be taken as an excuse for uncontrolled contamination of water resources. Effects of acute and chronic toxicity caused by pesticide use can be observed in humans and organisms in the ecosystem.